Panazz Players Please Pan Fans - Joseph, Terry (Express)
This is a review of a concert put on by the Panazz Players, Trinidad's top show-steelband. While the band executed intricate passages and solos on the double tenor pans, they were accompanied by several guest artistes.
Keywords: Concerts -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago